THE EFFECT OF THE EDUTAINMENT METHOD ON STUDENTS’ LEARNING ACHIEVEMENT IN THE SELF-DEVELOPMENT COURSE AT POLITEKNIK - Inna Hanarti; Mira Firlana; Nur Haris Ependi (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
The purpose of this study was to know (1) the impact of the Teams Games Tournament (TGT) and conventional learning models on the students history education achievement (2) to reveal the impact differences between the students with high and low learning independence on their history education achievement, and (3) to find out the interactional impact between the learning models on the students history education achievement and their independent learning. The research was carried out in SMA 1 Banyudono in the second semester of academic year 2012/2013. The study population was all students in class XI IPS SMA N 1 Banyudono, of the population of researchers got 32 students XI IPS 4 as the experimental group using the learning model of TGT and 32 students of class XI IPS 3 as control group using conventional learning. Sampling technique used was the cluster random. The data were analyzed with ANOVA multiple regression after precondition test. The normality analysis was tested using Lilliefors significant corection from Kolmogorov-Smirnov Test, meanwhile the homogeneity analysis with Levene's Test. From the results of this research concluded that: 1) There is a significant differing impact of TGT and conventional learning models on the students history education achievement, as shown by F value = 4.861, and p value = 0.31> 0.05. 2) a significant differing impact between students with high and low learning independence is found as reflected by F value = 40.822, and p value = 0.000 <0.05, and finally 3) there is no interactional impact between the learning models and the students independent learning in history education as confirmed by F value = 2.063, and p value = 0.129> 0.05. Based on this research, it can be concluded that the learning model, edutainment method, indoor and outdoor learning activities, and students’ learning motivation have a significant influence on students’ learning achievement in the Development of Self course. Keywords: Learning achievement, learning model, edutainment method, indoor-outdoor learning activities, learning motivation.